Initiation of Rotors by Fast Propagation Regions in Excitable Media: A Theoretical Study - Gao, Xiang; Krekhov, Alexei; Zykov, Vladimir; Bodenschatz, Eberhard (Frontiers in Physics, 2018)
We study the effect of geometry of a fast propagation region (FPR) in an excitable medium on the rotor initiation using a generic two-dimensional reaction-diffusion model. We find that, while the flat boundary of a rectangularly shaped FPR may block the propagation of the excitation wave, a large local curvature at the rounded corners of the FPR would prevent the blockage and thus initiate a rotor. Our simulations demonstrate that the prerequisites for the rotor initiation are the degree of the heterogeneity, its shape and size. These results may explain the incidence of arrhythmias by local heterogeneities induced, for example, by a cardiac tissue remodeling.